2006
DOI: 10.1080/00420980500409292
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Mobility of Elderly People in Different Urban Settings: The Example of the City of Bonn, Germany

Abstract: The social model for old age is a self-determined and socially integrated life for as long as possible. In this regard, different settings offer different conditions. The article investigates which living conditions best meet the needs of elderly people. It is based on results from the FRAME (leisure mobility of elderly people) research project, which examines the everyday mobility of persons aged 60 and older in different urban settings. The results show that an active lifestyle is possible in all the study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 16 publications
1
58
0
8
Order By: Relevance
“…However, existing sprawled land use patterns may make such large-scale community transformation and physical infrastructure development in society not feasible. Fobker and Grotz (2006) argued that the mere existence of commercial and support facilities within walking distance does not contribute to an intense usage of them by the elderly. Robert (2002), citing there has been an increasing transference of responsibility for health and social services from the federal government to states, and the states to municipalities, argued for the development of community-based supportive environments for the elderly to cope with such transition rather than a massive physical community transformation.…”
Section: Discussionmentioning
confidence: 99%
“…However, existing sprawled land use patterns may make such large-scale community transformation and physical infrastructure development in society not feasible. Fobker and Grotz (2006) argued that the mere existence of commercial and support facilities within walking distance does not contribute to an intense usage of them by the elderly. Robert (2002), citing there has been an increasing transference of responsibility for health and social services from the federal government to states, and the states to municipalities, argued for the development of community-based supportive environments for the elderly to cope with such transition rather than a massive physical community transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the elderly tend to avoid long distances or complex trips; therefore, an appropriate residential location, within reach of necessary services, may be more critical in old age than at any other time in life (Giuliano et al, 2003;Truong and Somenahalli, 2015). Urban environments with higher densities, diverse land-uses, and pedestrian-friendly streets are better poised to meet the needs of older people -especially as the importance of recreational-, social-, and shopping-related travel increases whereas the role of work-related trips declines (Chudyk et al, 2015;Cui et al, 2017;Fobker and Grotz, 2006;van den Berg et al, 2011;Van Holle et al, 2014;Winters et al, 2015).…”
Section: Built Environment Factorsmentioning
confidence: 99%
“…Urban environments with physical decay are considered the most vulnerable to attracting criminals (Wilson & Kelling, 1982). Föbker and Grotz (2006) and Herzog and Kirk (2005) reported that dark pathways in parks cause fear, especially amongst women and those who are susceptible to physical attack (e.g. the elderly and disabled).…”
Section: Parks As Criminogenic Placesmentioning
confidence: 99%